Brasile: territorio ed epidemia. Annotazioni: Il mondo e la lotta alla pandemia da COVID-19 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
This essay aims to provide an initial assessment on the territorial consequences of Brazilian Coronavirus epidemic’s management policies.
Keywords: Brazil; social space; COVID-19